Detection of circulating KRAS mutant DNA in extracellular vesicles using droplet digital PCR in patients with colon cancer - Choi, Jeesoo; Cho, Ho Yeon; Jeon, Jeongseok; Kim, Kyung-A; Han, Yoon Dae; Ahn, Joong Bae; Wortzel, Inbal; Lyden, David; Kim, Han Sang (Frontiers in Oncology, 2022)
Background: Extracellular vesicles secreted by tumor cells contain double-stranded DNA called extracellular vesicle DNA (evDNA). EvDNA is genomic DNA that reflects cancer driver mutations. However, the significance of evDNA analysis in the diagnosis and surveillance of colon cancer remains unclear. This study aimed to investigate the clinical utility of extracellular vesicles and evDNA isolated from the plasma of colon cancer patients harboring KRAS G12D and G13D mutations. Methods: Cell-free DNA (cfDNA) and evDNA were collected from the plasma of 30 patients with colon cancer. KRAS mutation status (G12D and G13D) was detected using a droplet digital polymerase chain reaction assay (ddPCR). Sensitivity and specificity were evaluated in patients with wild-type KRAS tumors. Mutation status was correlated with carcinoembryonic antigen (CEA) levels and overall survival (OS). Results: Thirty cfDNA and evDNA pairs showed a KRAS fractional abundance (FA) ranging from 0 to 45.26% and 0 to 83.81%, respectively. When compared with eight wild-type KRAS samples, cfDNA exhibited 70% sensitivity and 100% specificity, whereas evDNA achieved 76.67% sensitivity and 100% specificity. The concentration of evDNA was significantly lower than that of cfDNA, but it obtained a higher FA than cfDNA, while showing a positive correlation with CEA. Conclusions: Our findings demonstrate the feasibility of evDNA as a complementary tool to aid current methods of patient evaluation in the diagnosis and surveillance of colon cancer.